2021
DOI: 10.1155/2021/4504363
|View full text |Cite
|
Sign up to set email alerts
|

Destructive Effects of Pyroptosis on Homeostasis of Neuron Survival Associated with the Dysfunctional BBB-Glymphatic System and Amyloid-Beta Accumulation after Cerebral Ischemia/Reperfusion in Rats

Abstract: Neuroinflammation-related amyloid-beta peptide (Aβ) accumulation after cerebral ischemia/reperfusion (I/R) accounts for cerebral I/R injuries and poststroke dementia. Recently, pyroptosis, a proinflammatory cell death, has been identified as a crucial pathological link of cerebral I/R injuries. However, whether pyroptosis acts as a trigger of Aβ accumulation after cerebral I/R has not yet been demonstrated. Blood-brain barrier (BBB) and glymphatic system mediated by aquaporin-4 (AQP-4) on astrocytic endfeet ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…Although they did not directly investigate the associated changes in AQP4, in a previous study, using the same PSD model the group found delocalization of AQP4 channels that was associated with Aβ aggregation and increased astrogliosis within the thalamus and hippocampus 2 weeks following surgery [ 221 ]. Interestingly, a recent study investigating the effects of inflammation associated cell death within the ischaemic core of rats following MCAo with reperfusion, discovered that neuroinflammation following a stroke promoted the loss of BBB integrity and AQP4 polarization, Aβ accumulation, and the formation of Aβ 1–42 oligomers [ 222 ]. These studies highlight that impairment in AQP4 and the associated dysfunction of the GS play a key role in the aggregation of neurotoxic proteins in both the ischaemic core and sites of SND.…”
Section: Neuroinflammation In Sndmentioning
confidence: 99%
“…Although they did not directly investigate the associated changes in AQP4, in a previous study, using the same PSD model the group found delocalization of AQP4 channels that was associated with Aβ aggregation and increased astrogliosis within the thalamus and hippocampus 2 weeks following surgery [ 221 ]. Interestingly, a recent study investigating the effects of inflammation associated cell death within the ischaemic core of rats following MCAo with reperfusion, discovered that neuroinflammation following a stroke promoted the loss of BBB integrity and AQP4 polarization, Aβ accumulation, and the formation of Aβ 1–42 oligomers [ 222 ]. These studies highlight that impairment in AQP4 and the associated dysfunction of the GS play a key role in the aggregation of neurotoxic proteins in both the ischaemic core and sites of SND.…”
Section: Neuroinflammation In Sndmentioning
confidence: 99%
“…However, different from BHD and TXL, YZFDF is purely composed of several plant-derived natural products, but the preliminary results in the present study showed that YZFDF could also exert significant neuroprotective effects against cerebral I/R injury by dose-dependently alleviating neurological deficits and cerebral infarct after reperfusion. Our previous work revealed that pyroptosis of glial cells (microglia and astrocytes) is a considerable pathological mechanism causing BBB damage after cerebral I/R, and abating pyroptosis contributes to protect against BBB breakdown and maintains the homeostasis of brain microenvironments ( Lyu et al, 2021 ). Our present study further indicated that YZFDF could protect ischemic cerebral tissues against pyroptotic cell death and accordingly exert protective effects against BBB collapse in damaged cortex and hippocampus areas after cerebral I/R, potentially promoting blood flow reperfusion in microcirculation of ischemic cerebral tissues, which probably owed to the multiple efficacies of invigorating Qi, removing blood stasis, and dredging brain collaterals.…”
Section: Discussionmentioning
confidence: 99%
“…However, emerging literature has proven that caspase-11/GSDMD-mediated noncanonical pyroptosis is involved in acute kidney injury and hepatic injury induced by some endogenous pathophysiological factors including I/R injury ( Miao et al, 2019 ; Wang X. et al, 2020 ). Our recent work revealed that caspase-11/GSDMD-mediated noncanonical pyroptosis also involves in cerebral I/R injury ( Lyu et al, 2021 ). In the present study, we observed that YZFDF could obviously inactivate caspase-11 as well as cut off NLRP3/ASC/caspase-1 signaling and thus inhibit the cleavage of GSDMD to reduce the formation of GSDMD-N, indicating that YZFDF could exert inhibitory effects on cerebral I/R–induced canonical and noncanonical pyroptosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations